Investigating Food Names Translation of Restaurant and Café Menus - Azzahra, Yoanita; Kholifah, Asrofin Nur; Pascarina, Hanifa (PAROLE: Journal of Linguistics and Education, 2024)
This research investigates the translation of food names on menu lists by employing a Linguistic Landscape approach, focusing on public spaces such as restaurants and cafes. The goal is to recognize the categorization of menu types and structures and to identify the translation methods. Four types of menu classification are found in the menu list, and more frequently provided to cater to the requirements of the local community. The usage of menu types is evenly distributed across food in the Northern Purwokerto area, starting from bite-sized food to traditional food. The menu types tend to be used in Western culture and are rarely applied to Indonesian food conditions. The prevalence of main courses as a predominant menu structure is attributed to the common preference among Indonesians for substantial meals. Therefore, various dining establishments adapt to the cultural preferences prevalent in their surroundings. There is also a descriptive translation method being the most commonly employed. It involves providing a detailed of the process and elaborating on the food menu by explaining how the dishes are served. Moreover, the food menu served aligns with the local culture, characterized by a prevalence of hearty portions.